P795 Prevalence and etiology of post-azithromycin persistent non-gonococcal urethritis (NGU) symptoms in men. (14th July 2019) - Jordan, Stephen; Toh, Evelyn; Batteiger, Teresa; Williams, James; Fortenberry, Lora; Batteiger, Byron; Nelson, David
Abstract : Background: Persistent NGU occurs when symptoms persist after empiric NGU treatment and has been associated with Mycoplasma genitalium (MG) infection. The prevalence and etiology of persistent NGU in men remains largely unknown. Methods: Within the Idiopathic Urethritis Men's Project cohort study, we recruited men with NGU. NGU was diagnosed by the presence of urethritis signs and/or symptoms and urethral Gram stain with ≥ 5 PMN/HPF. Men were treated with 1 gm azithromycin and returned for a 1-month test-of-cure visit. At the test-of-cure visit, men were asked about post-treatment symptom outcomes and partner treatment. A first-catch urine specimen was obtained at both visits for five-pathogen testing for Neisseria gonorrhoeae (NG), Chlamydia trachomatis (CT), MG, Trichomonas vaginalis (TV), and Ureaplasma urealyticum (UU). NG-positive cases were excluded and five-pathogen-negative cases were classified as idiopathic urethritis (IU). Post-treatment symptom outcomes were: (1) resolved, (2) resolved then recurred, or (3) persisted unchanged. Results: One hundred twenty-four men are included in this study. The median age was 28, 52% were African American, and 86% self-identified as heterosexual. All men reported urethral symptoms and 98% had a discharge on exam at baseline. Symptoms resolved completely in 91 (73%) men. Symptoms resolved then recurred or persisted unchanged in 12 (10%) and 21 (17%) men, respectively. Excluding men with untreated partners (N = 9, 28%), a different pathogen was identified in 5 (50%) and 4 (25%) men with recurrent and persistent symptoms, respectively. In men with the same pathogen identified (N = 15), 53% were IU, 33% were MG, 7% were CT, and 7% were UU. Conclusion: Persistent NGU occurs in approximately 25% of azithromycin-treated men and is related to a new infection in up to 50% of cases. In men with persistent symptoms and the same infection identified at the test-of-cure visit, MG and IU comprised 86% of cases, which suggests that MG and IU-associated organisms may be resistant to azithromycin. Disclosure: No significant relationships.